1980
DOI: 10.1136/sti.56.4.259
|View full text |Cite
|
Sign up to set email alerts
|

Contact-tracing in patients with genital chlamydial infection

Abstract: SUMMARY Of 2021 men attending a venereal disease clinic during a 20-month period, 527 (26' 1 07) harboured Chlamydia trachomatis, 310 (15 a 3%) Neisseria gonorrhoeae, and 94 (4' 7%) both organisms. C trachomatis and N gonorrhoeae were isolated in 163 (15' 707o) and 141 (13 -807o) respectively of 1039 women attending the same clinic over a one-year period; 44 (4' 2%) women harboured both organisms.Contact-tracing was carried out for 112 male and 88 female patients infected with chlamydia, none of whom had go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Establishing STI clinical services in non‐clinical, institutional or community settings is typically more expensive than clinic‐based approaches but can yield substantial benefits if services are extended to persons at higher than average risk of acquiring or transmitting STIs within communities 13,14 . Previous studies in Sweden have shown that attendance rates for identified partners of C. trachomatis –infected patients in primary health care setting changed from 72% in 1980 (before the Communicable Diseases Act) 15 to 99% in 1993 4 . However, there have previously been few measurements of the effectiveness of the partner notification carried out by the youth health centres in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing STI clinical services in non‐clinical, institutional or community settings is typically more expensive than clinic‐based approaches but can yield substantial benefits if services are extended to persons at higher than average risk of acquiring or transmitting STIs within communities 13,14 . Previous studies in Sweden have shown that attendance rates for identified partners of C. trachomatis –infected patients in primary health care setting changed from 72% in 1980 (before the Communicable Diseases Act) 15 to 99% in 1993 4 . However, there have previously been few measurements of the effectiveness of the partner notification carried out by the youth health centres in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…This regimen does not delay the abortion if C. trachomatis is identified by rapid immunological methods rather than by culture. To avoid reinfection, sexual partners ought to be identified and treated (Thelin et al . 1980; Westrøm 1982).…”
Section: Discussionmentioning
confidence: 99%
“…14,23 However, this is lower than the proportion due to asymptomatic disease reported in the literature regarding adolescent women with chlamydia. This is consistent with reports in adult women that 30-80% of chlamydial urogenital infections are asymptomatic, 21,22 as are 20-40% of gonococcal infections.…”
Section: -20% Of Infantsmentioning
confidence: 74%